Educação e políticas públicas de redução de riscos e danos do uso abusivo de bebidas alcoólicas entre estudantes universitários - Maurina, Leda Rúbia Corbulim (2007)
The alcohol s excessive use, subject of many current discussions, have been presented in media, showing that its analysis is a social need. The education, as a social action, becomes co-responsible for this question s future. This study is among the publics politicizes addressed to the educations of a specific young group in graduation s process: The universities students. The approach had the following objects: To know the perception of this people about the risks that they can be expose when use alcohol excessively, to investigate some of the underlying reasons of this substance s use and to visualize pedagogic actions possibilities, turned to this risks reduction, elapsing of the excessive use of alcoholic drinks. Therefore, the focal group method and supplementary questions were utilized; to the information s treatments, later, was developed the content analysis of this questions. The universities speech s emerging categories, exploded as underlying reasons of the use, the families importance, the alcohol as a social lubricant , the media s influence, the parties and universities contexts and the academic s life tensions relief. The students identified as risks of the excessive use of alcohol drinks: physical damage, alcohol dependence and others drugs use, academic s performance loss and in the familiar relationship. As actions to be implemented in university, the young suggested partnerintegration, cultural-recreational and advertising-reflexive activities, integrated in an institutional policy, involving in this build and performance, all the academic community. This investigation provides a reflection about the importance of the researches that involve this problematic to subsidize prevention s programs and policies to the abusive use of alcohol and others drugs in university context. The research showed the pedagogic and social university s function in organize pedagogic actions of risks and damages reduction in integral young s formation, through their educations related with the use of drinks alcohols critically, to that they can think about the possibilities to relieve their tensions and to make the integrations and commemorations without the exhibition to the alcohol excessive use, as well as it s consequences